Hardware hacking have fun while voiding your warranty - Grand, Joe.; Russell, Ryan, 1969-; Syngress Media, Inc. (Rockland, MA : Syngress Pub., 2004)
"If I had this book 10 years ago, the FBI would never have found me!"--Kevin Mitnick This book has something for everyone---from the beginner hobbyist with no electronics or coding experience to the self-proclaimed "gadget geek." Take an ordinary piece of equipment and turn it into a personal work of art. Build upon an existing idea to create something better. Have fun while voiding your warranty! Some of the hardware hacks in this book include: * Don't toss your iPod away when the battery dies! Don't pay Apple the $99 to replace it! Install a new iPod battery yourself without Apple's "help" * An Apple a day! Modify a standard Apple USB Mouse into a glowing UFO Mouse or build a FireWire terabyte hard drive and custom case * Have you played Atari today? Create an arcade-style Atari 5200 paddle controller for your favorite retro videogames or transform the Atari 2600 joystick into one that can be used by left-handed players * Modern game systems, too! Hack your PlayStation 2 to boot code from the memory card or modify your PlayStation 2 for homebrew game development * Videophiles unite! Design, build, and configure your own Windows- or Linux-based Home Theater PC * Ride the airwaves! Modify a wireless PCMCIA NIC to include an external antenna connector or load Linux onto your Access Point * Stick it to The Man! Remove the proprietary barcode encoding from your CueCat and turn it into a regular barcode reader * Hack your Palm! Upgrade the available RAM on your Palm m505 from 8MB to 16MB Includes hacks of today's most popular gaming systems like Xbox and PS/2. Teaches readers to unlock the full entertainment potential of their desktop PC. Frees iMac owners to enhance the features they love and get rid of the ones they hate.
Includes index.
Keywords: Microcomputers -- Maintenance and repair; Microcomputers -- Upgrading; Computer input-output equipment; Computer hackers; Reverse engineering; Electronic books